2019
DOI: 10.1111/jam.14212
|View full text |Cite
|
Sign up to set email alerts
|

Role of diverse fermentative factors towards microbial community shift in ruminants

Abstract: Summary Besides the liver, rumen is one of the most important components of metabolism in ruminants. However, the microbes residing in the rumen are influenced by several complex factors such as diet, which result in fluctuations in the rumen pH. Rumen pH affects feed intake and feed digestibility, subsequently causing microbial shift in the individual members of microbial community residing in the foregut and hindgut. This in turn causes an increase in lipopolysaccharide concentration, among other factors, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Clostridiales and Bacteroidales), our statistical elaboration depicted a negative correlation with the diversity of the milk microbiomes. Such chemicals have a dose‐dependent inhibitory effect towards several bacterial groups, because of the diffusion through the cell membrane and further dissociation at the cytoplasm level (Faniyi et al ., 2019). Narrowing the investigation to LAB, we confirmed that most of the above farming conditions and physicochemical parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Clostridiales and Bacteroidales), our statistical elaboration depicted a negative correlation with the diversity of the milk microbiomes. Such chemicals have a dose‐dependent inhibitory effect towards several bacterial groups, because of the diffusion through the cell membrane and further dissociation at the cytoplasm level (Faniyi et al ., 2019). Narrowing the investigation to LAB, we confirmed that most of the above farming conditions and physicochemical parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in SCFA with decreasing roughage indicates that there was higher digestibility, which enhanced microbial proliferation and metabolites. Ruminal pH is a parameter that indicates the state of acidity and alkalinity of the rumen, and could be used to predict the type of diet fed to animal (Faniyi et al ). In this study, despite the increase in digestibility of high‐ concentrate diet, the pH was within the optimal range of 6·0–6·8 (Kamra ; Ososanya et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Optimal rumen health is a prerequisite for animal welfare and profitable production. A rumen is healthy when there are abundance of favourable/beneficial microbes, large rumen papillae for an efficient nutrient absorption, possesses good barrier function and support good fibre digestibility (Faniyi et al ) and a well‐regulated rumen pH. The pH is a direct homoeostatic result of the acid–base balance regulation efforts of the rumen and the host (Aschenbach et al ).…”
Section: Introductionmentioning
confidence: 99%